Biomaterials in Guided Bone and Tissue Regenerations: An Update. (5th May 2022) - Namanloo, Reza Abdollahi; Ommani, Maedeh; Abbasi, Kamyar; Alam, Mostafa; Badkoobeh, Ashkan; Rahbar, Mahdi; Arasteh, Hadi Kokabi; Hajmohammadi, Emran; Soufdoost, Reza Sayyad; Mosaddad, Seyed Ali
Abstract : Purpose . Guided tissue reconstruction can be performed to restore the supporting structure of a previously lost tooth, which, in addition to maintaining beauty, preserves the function of the tooth in the patient. Materials and Methods . In this review, Scopus, PubMed, and MEDLINE databases were searched using the keywords "biocompatible materials, " "membrane, " "bone regeneration, " "tissue reconstruction, " and "dental biomaterials." Overall, 150 articles were reviewed, and finally, 107 articles published during 2000–2021 were included in the final paper. Results . Studies have been conducted on a variety of membranes in both clinical and experimental settings. The first half of this article explores the different kinds of membranes and diverse classes of biomaterials used in these procedures. Secondly, biomaterials are examined for their therapeutic uses such as growth factors, stem cells, and gene delivery vehicles. Conclusion . If a tooth has been extracted or if the gums have been infected with periodontal disease, guided bone regeneration procedures may be used to restore the lost bone. Recent years have seen a variety of approaches to regenerating these tissues. To prevent nonossifying cells from entering, membranes are heavily employed during guided rebuilding.